Association between Corrected QT Interval, QT Dispersion and Clinico-biochemical Severity of Diabetic Ketoacidosis in Children Aged 1-12 Years: A Prospective Cohort Study - Hamritha Ashokkumar; A Suriya; Shreenivas RachakondaPoovazhagi; Shreenivas Rachakonda; Shreenivas Rachakonda (Journal of Clinical and Diagnostic Research)
Introduction: Diabetic Ketoacidosis (DKA) is a serious complication in children with type 1 diabetes, characterised by hyperglycaemia, metabolic acidosis and ketosis. It often leads to cardiac arrhythmias due to electrolyte imbalances and prolonged corrected QT interval (QTc). Aim: To investigate the frequency of QTc prolongation and QT dispersion (QTd) in paediatric DKA patients and their relationship with serum electrolytes and pH. Materials and Methods: A prospective cohort study was conducted over a one-year period (August 2022 to August 2023) in the paediatric Intensive Care Unit (ICU) of the Institute of Child Health and Hospital for Children, Egmore, Chennai, Tamil Nadu, India. The study included 150 children aged 1 to 12 years diagnosed with DKA. Electrocardiograms (ECGs) were recorded both at presentation and after recovery from DKA, with QTc and QTd evaluated using a 12-lead ECG. The Mann-Whitney U test was employed to compare medians and Interquartile Ranges (IQR) between two groups, while Spearman’s correlation coefficient was used to assess relationships between variables, with results illustrated through a scatter plot. A p-value <0.05 was considered statistically significant. Results: Significant correlations were found between prolonged QTc intervals and severe acidosis, with affected patients exhibiting lower bicarbonate levels and higher anion gaps and blood ketone levels. After treatment, both QTc intervals and QTd significantly decreased, indicating improved cardiac repolarisation. Strong positive correlations were noted between QTc intervals and both the anion gap and blood ketone levels. Conclusion: The study highlights the QTc prolongation and QTd in children with DKA, which are closely linked to metabolic derangements. Routine ECG monitoring is essential for the early detection of QT prolongation, aiding in the prevention of life-threatening arrhythmias and improving patient outcomes.